Modern enabling techniques and adsorbents based dye removal with sustainability concerns in textile industrial sector -A comprehensive review. (1st November 2020) - Hynes, N. Rajesh Jesudoss; Kumar, J. Senthil; Kamyab, Hesam; Sujana, J. Angela Jennifa; Al-Khashman, Omar Ali; Kuslu, Yasemin; Ene, Antoaneta; Suresh Kumar, B.
Abstract: Wastewaters from the textile industry are hazardous effluents containing toxic complex components that without appropriate treatment severely impact the environment; causing harmful effects to the aquatic ecosystems, as well as to human health. The present study extensively reviews the dyes and chemicals utilized in the textile industry focusing on the traditional treatment methods -chemical, biological, physical and hybrid systems-for their removal from industrial wastewaters. In addition, a critical analysis on Internet of Things based management systems for their remote monitoring and control of the water quality is reported. It was found the absence of a common platform for the integration of the different traditional treatment methods in association with modern technologies is the main limiting factor for an effective sustainable manufacturing. Therefore, it is the aim of this research to broaden the scope of potential solutions, proposing cost-effective high-performing combined strategies with promising benefits for future industrial applications. Graphical abstract: Image 1 Highlights: Effective ways of removal of dye in textile effluents are reviewed. Internet of Things based enabling techniques included. Sensors with advanced controllers are studied. Full potential of low cost of adsorbents are explored.